Usulan Strategi Bisnis untuk Meningkatkan Keunggulan Kompetitif Usaha Pada Startup Prove Fragrance dengan Menggunakan Metode SWOT - Indah Br Simamora; Agus Maolana Hidayat (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study delves into understanding the factors contributing to the sales decline experienced by the rebranded cosmetics startup "Prove." Employing qualitative research and fishbone diagram techniques, four primary root causes emerged: insufficient product information dissemination, limited product variety, underutilized digital marketing, and a lack of robust business development strategies. The proposed solution involves crafting a more effective business development strategy, recognizing that Prove lacked a well-defined approach to enhance its competitive advantage. The research emphasizes a SWOT analysis of Prove, focusing on its internal and external environment. The study, centered around Prove's Bandung office, involves the CEO and several employees as the unit of analysis. Collected through in-depth interviews, field observations, and documentation. The results highlight Prove's strengths in innovative product design and creative opportunities for partnerships and business expansion.